ITS Reconstruction Tool-Suite: An inverse algorithm package for industrial process tomography. (December 2015) - Wei, Kent; Qiu, ChangHua; Soleimani, Manuchehr; Primrose, Ken
Abstract: Electrical resistance tomography (ERT) and electrical capacitance tomography (ECT) are two established process tomography techniques that can be applied into various indsutries. ERT can monitor the electrical conductivity changes in the process whereas ECT can detect the electrical dielectric materials. Due to their high-speed and low cost features, they are particularly attractive to industrial applications which require real time conditional monitoring. For the past decades, 2D linear back projection (LBP) has been the standard technique for both commercialised ERT and ECT systems because of its simplicity and fast reconstruction speed. In this paper, ITS Plc has released a 'Reconstruction Tool-Suite' software that allows industrial users to utilise different reconstruction algorithms to further understand their processes. Different algorithms are integrated into this software package including the single step Tikhonov method and the iterative Landweber method. In the latest version of the software, the full-field 3D tomography reconstruction scheme is also included, which allows the users to perform 3D reconstruction for their processes. A series of experiments are conducted to validate the pros and cons of different methods.